(untitled) (Research, Society and Development, 2020)
This study aims to expose the Google Classroom tool as an innovative element, making it possible to streamline teaching and bringing students closer to content in order to make them protagonists of their own learning. Currently, there are many professionals who have the mastery of inserting technology in the classroom, but the great challenge is to know how to turn this practice into an integrative and social environment. Even with the evolution of new technologies, there are still some focuses that make the use of these practices limited in many institutions, one of the points is the lack of knowledge and training on the part of teachers. When dealing with the insertion of technology in institutions or even adopting a teaching methodology, it is necessary to analyze situations that may promote the discussion of entry and permanence of this innovative model. We cannot just think that teaching becomes innovative if the educational officer inserts this methodology in a non-pedagogical way. To answer the proposal for the integration of the Google Classoom tool in the learning process, we opted for a systematic descriptive review and as a database model were used: Google academic and Brazilian Digital Library of Theses and Dissertations (BDTD). With this research we concluded that, with the use of google classroom, the teacher will be able to find multiple methodological ways, leaving the virtual classroom open 24 hours, stimulating the interest and participation of the students, being the mentioned tool an instrument capable of modifying the relations teaching and learning within and outside the educational sphere.